Longitudinal Association of Non‐Alcoholic Fatty Liver Disease With Changes in Myocardial Structure and Function: The CARDIA Study - Lisa B. VanWagner; Jane E. Wilcox; Hongyan Ning; Cora E. Lewis; John Jeffrey Carr; Mary E. Rinella; Sanjiv J. Shah; Joao A. C. Lima; Donald M. Lloyd‐Jones (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Non‐alcoholic fatty liver disease (NAFLD) is associated with high cardiovascular morbidity/mortality, including heart failure. Abnormalities in left ventricular (LV) structure/function are associated with heart failure risk. Methods and Results Participants from the population‐based CARDIA (Coronary Artery Risk Development in Young Adults) study year 25 exam (2010–2011, aged 43–55 years, 61% women, 48% black) with computed tomography measured liver fat and comprehensive echocardiography were included. Echocardiography was repeated at year 30 follow‐up (aged 47–62 years, N=1827). NAFLD was defined as liver attenuation ≤40 HU after exclusions. LV geometry was classified into normal and abnormal by integrating relative wall thickness and LV mass index. Diastolic function was defined using Doppler and tissue Doppler imaging. Systolic function was assessed with myocardial strain measured by speckle tracking. NAFLD prevalence was 8.7% (n=159). NAFLD participants had higher LV mass, relative wall thickness, incident LV hypertrophy and abnormal LV geometry versus non‐NAFLD (P<0.02). NAFLD participants had impaired LV relaxation (E/A ratio 1.1 versus 1.2), higher LV filling pressures (E/e′ ratio 7.9 versus 7.2), worse longitudinal strain (−13.9% versus −15.3%), and lower LV ejection fraction (58.9% versus 60.2%, P<0.01). In multivariable analyses adjusted for heart failure risk factors, NAFLD was independently associated with incident LV hypertrophy (odds ratio: 1.9, 95% CI: 1.1–3.4), abnormal LV geometry (odds ratio: 1.9, 1.1–3.3) and greater change in strain (odds ratio: 2.2, 1.1–4.7). Adjustment for body mass index attenuated associations to non‐significance. Conclusions NAFLD is associated with subclinical changes over time in LV structure/function and obesity explains much of the association. Presence of obesity in mid‐life may identify an important at‐risk population in whom to focus preventive heart failure strategies.